4D printing of self-folding and cell-encapsulating 3D microstructures as scaffolds for tissue-engineering applications. (4th August 2020) - Cui, Chunxiao; Kim, Dong-Ook; Pack, Min Y.; Han, Biao; Han, Lin; Sun, Ying; Han, Li-Hsin
Abstract: Technology of tissue-engineering advanced rapidly in the last decade and motivated numerous studies in cell-engineering and biofabrication. Three-dimensional (3D) tissue-engineering scaffolds play a critical role in this field, as the scaffolds provide the biomimetic microenvironments that could stimulate desired cell behaviors for regeneration. However, despite many achievements, the fabrication of 3D scaffold remains challenging due to the difficulty of encapsulating cells in 3D scaffolds, controlling cell-cell organization in 3D, and being adapted by users unfamiliar with 3D biofabrication. In this study, we circumvent these obstacles by creating a four-dimensional (4D) inkjet-printing platform. This platform produces micropatterns that self-fold into a 3D scaffold. Seeding live cells uniformly onto the micropatterns before self-folding leads to cell-encapsulating 3D scaffolds with layer-wise cell-cell organization. Photo-crosslinkable biomaterial-inks of distinct swelling rates were synthesized from gelatin, and the biomaterial-inks were patterned by a customized high-precision inkjet-printer into bilayer micropatterns that were capable of self-folding into 3D microstructures. A mathematical model was developed to help design self-folding and to aid the understanding of the self-folding mechanism. Human umbilical vein endothelial cells (HUVECs) were embedded in self-folded microtubes to mimic microvessels. HUVECs in the microtube spread, proliferated, showed high cell viability, and engrafted on the microtube's inner wall mimicking the native endothelial cells. For physician and biologist end-users, this 4D printing method provides an easy-to-use platform that supports standard two-dimensional cell-seeding protocol while enabling the users to customize 3D cellularized scaffold as desired. This work demonstrated 4D printing as a promising tool for tissue-engineering applications.